The state of the art in student engagement - Chris Howard (Frontiers Research Topics, 2015)
There is an extensive literature conducted from a range of theoretical perspectives and methodologies on the role of groups and student learning in higher education. However here the concept of the 'group' is heavily contested at a theoretical level but within higher education practice, characterizing the group has tended to be clear cut. Groups of students are often formed within the parameters of specific educational programs to address explicitly defined learning objectives. These groups are often small scale and achieve tasks through cooperative or collaborative learning. Cooperative learning involves students dividing roles and responsibilities between group members, so learning becomes an independent process and outcome. On the other hand, collaborative learning involves students working together by developing shared meanings and knowledge to solve a task or problem. From this perspective, learning is conceptualized as both a social process and individual outcome. That is, collaborative learning may facilitate individual student conceptual understanding and hence lead to higher academic achievement. The empirical evidence is encouraging as has been shown that students working collaboratively tend to achieve higher grades than students working independently. However the above perspectives on student engagement assume that groups are formed within the confines of formal learning environments (e.g. lecture theaters), involve students on the same degree program, have the explicit function of achieving a learning task and disband once this has been achieved. However, students may also use existing social networks such as friendship groups as a mechanism for learning, which may occur outside of formal learning environments. There is an extensive literature on the role and benefits of friendship groups on student learning within primary and secondary education but there is a distinct lack of research within higher education. This ebook is innovative and ambitious and will highlight and consolidate, the current understanding of the role that student based engagement behaviors may serve in effective pedagogy. A unique aspect of this research topic will be the fact that scholars will also be welcome to submit articles that describe the efficacy of the full range of approaches that have been employed to facilitate student engagement across the sector.